Solar panel optimization using maximum power point tracking based on Artificial Bee Colony algorithm - Hartono Hartono; Yusraini Muharni; Wahid Diana Tasdik; Alief Maulana; Irma Saraswati (Universitas Sultan Ageng Tirtayasa, 2022)
Solar panels are a renewable energy generator widely used by the wider community. However, solar panels have a disadvantage in operation, namely very low efficiency. One way to improve the performance of solar panels is to find the MPP (Maximum Power Point) on the V-P curve of the solar panel. This study aims to find the maximum point of the solar panel so that the output power is maximized. This research has succeeded in making a model of a solar panel-based MPPT system using the Artificial Bee Colony method using a DC-DC converter of the choke type. The model is made using Solarland 200 WP solar panels. The difference in output power based on the test results obtained the results of the power efficiency generated by solar panels using MPPT on changes in irradiation with an average fixed temperature of 99.06%. At temperature changes with constant irradiation, the average is 99.12%.